2019
DOI: 10.3390/ijerph16214164
|View full text |Cite
|
Sign up to set email alerts
|

A Retrospective Investigation on Age and Gender Differences of Injuries in DanceSport

Abstract: In spite of the extensive research on incidence site and type of injury in ballet and modern dancers, limited studies on injury in DanceSport have been reported. Therefore, this study determined retrospectively (within last 12 months) incidence, severity, site and type of injury, between gender and age-class in DanceSport. Participants were 97 international sport-dancers (female, 41; male, 56). Sixty-six (69%) dancers reported 96 injuries (1.00 (range = 4)) injuries per dancer) and an injury incidence of 1.7 (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 38 publications
0
5
2
Order By: Relevance
“…However, to the best of our knowledge, this is one of the first studies which examined gender as a possible factor of injury exclusively in adolescent dancers. This probably explains the discrepancy between our findings and those of previous studies where female dancers were reported to have a greater injury risk than their male peers [ 26 , 27 ]. We must highlight the fact that those studies involved older adolescents and adult dancers.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…However, to the best of our knowledge, this is one of the first studies which examined gender as a possible factor of injury exclusively in adolescent dancers. This probably explains the discrepancy between our findings and those of previous studies where female dancers were reported to have a greater injury risk than their male peers [ 26 , 27 ]. We must highlight the fact that those studies involved older adolescents and adult dancers.…”
Section: Discussioncontrasting
confidence: 99%
“…This is in certain disagreement with previous reports that mostly identified a higher risk for injury among female dancers. For example, an international study revealed that females had a significantly higher median injury incidence than males and confirmed that there were gender differences regarding reported traumatic injuries, with a higher incidence of traumatic injuries occurring in females (74.6%) than males (46.7%) [ 27 ]. Supportively, another study showed that female dancers have a higher injury risk than their male counterparts [ 26 ].…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…On the other hand, risk and incidence of overuse injuries in dancers were previously found to be positively associated with years of dance training and increased training time 25–27. However, our findings and two other studies found insignificant relationships between age and CAI 28 29. The inconsistent findings may be due to differences in injury history, activity or training load between studies, and varying study methodologies.…”
Section: Discussioncontrasting
confidence: 81%
“…This finding was partially supported by Koutedakis and colleagues ( Koutedakis and Sharp, 2004 ) who reported that hamstring and quadriceps muscle strengthening is beneficial to professional ballerinas because of the increased thigh muscle torque and also the prevention of muscle torque decrements after dance routines. This suggested an important message for dance educators and dancers that muscle strengthening is an essential component for prevention of injury, and they should know how to implement it into their training routine effectively ( Premelč et al, 2019 ). Unfortunately, the self-report design of this study did not allow us to define what kinds of strengthening exercises were, or should be, performed by ballet dancers.…”
Section: Discussionmentioning
confidence: 99%